A cleaning and reusable biochemical degumming method for hemp fibers through immobilized pectinase lyase on calcium alginate microspheres. (24th November 2022) - Zhang, Xin; Guo, Jing; Yu, Yue; Hao, Xinmin; Guan, Fucheng; Zhang, Sen
Abstract : A biochemical degumming solution (chemical auxiliaries & CA-PL) can be used twice; the chemical auxiliaries swelled the fibers and CA-PL acted on the pectin layer to extract cellulose. Abstract : The traditional extraction technique for hemp fibers results in high energy consumption, serious pollution, excessive degumming and strength loss. Herein, a cleaning and reusable biochemical degumming method is provided, which combines calcium alginate microspheres loaded with pectinase lyase (CA-PL) and a small number of chemical auxiliaries. This biochemical degumming method has a shorter reaction time and lower reaction temperature and is environmentally friendly. Complete degumming can be achieved by repeating this method two to three times. The effect of the number of uses of the biochemical degumming solution on the composition, mechanical properties and strength of the resulting hemp fibers was studied. The biochemical degumming solution could be reused three times; the extraction rates of cellulose after each degumming treatment were 77.09%, 76.94% and 70.61%, and the breaking strength was 64.3 cN dtex −1, 62.1 cN dtex −1 and 59.7 cN dtex −1, respectively. The results of repeated degumming treatment showed that the optimal number of recycles of the biochemical degumming solution was two; the degumming efficiency was higher and the cellulose extraction degree was better.